(3GdJObjb GdNGQLj heMGaX GdMSGHGJ aj GdLRGFQ (B/s - (3CbGSe, YeQs ((3GdLRGFQ(B: s (3OGQ GdcJGH GdYQHj(B, s, 2016)
(3GSJgd gGPG GdcJGH HeGgjI GdJObjb GdNGQLj ef NdGd eaghe GdeQGLYI GdNGQLjI , CgOGagG , CfhGYgG heSDhdjGJ GdeQGLY GdNGQLj, efgLjI GdeQGLYI GdNGQLjI, Jbjje fXGe GdQbGHI GdOGNdjI, EYOGO GdJbQjQ hedaGJ GdYed, hGbY egfI GdJObjb GdNGQLj aj GdLRGFQ , GdfUhU GdbGfhfjI GdefXeI degfI GdJObjb, GdJZjjQGJ GdgjcdjI ddefXeGJ GdegfjI aj GdLRGFQ ef NdGd GdgjcdI GdLOjOI ddeLdS GdhWfj ddeMGSHI, OhQ hegGe GdefXeGJ GdegfjI aj Xd GdEUdGM GdeMGSHj aj GdLRGFQ, VhGHW egfI eMGaX GdMSGHGJ aj GdLRGFQ, GdNUGFU GdYGeI GdeJYdbI HgG hefgLjI Yed eMGaX GdMSGHGJ hab GdGLJgGOGJ GdegfjI aj GdLRGFQ, CJYGH GdeQGLY hBOGH hSdhc GdegfI hGdeYGjjQ GdOhdjI hGdeMdjI dEYOGO JbQjQ eMGaX GdMSGHGJ(B.s
(3eQGLY U(B.191s
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs